Defining Low Prognosis Patients Undergoing Assisted Reproductive Technology: POSEIDON Criteria—The Why - Esteves, Sandro C.; Roque, Matheus; Bedoschi, Giuliano M.; Conforti, Alessandro; Humaidan, Peter; Alviggi, Carlo (Frontiers in Endocrinology, 2018)
Women with impaired ovarian reserve or poor ovarian response (POR) to exogenous gonadotropin stimulation present a challenge for reproductive specialists. The primary reasons relate to the still limited knowledge about the POR pathophysiology and the lack of practical solutions for the management of these conditions. Indeed, clinical trials using the current standards to define POR failed to show evidence in favor of a particular treatment modality. Furthermore, critical factors for reproductive success and number of oocytes collected after ovum pickup such as age-dependent embryo aneuploidy rates and intrinsic ovarian resistance to gonadotropin stimulation are not taken into consideration by the current POR criteria. As a result, the accepted definitions for POR have been criticized for their inadequacy concerning the proper patient characterization and for not providing clinicians a guide for therapeutic management. A novel system to classify infertility patients with "expected" or "unexpected" inappropriate ovarian response to exogenous gonadotropins -the Poseidon criteria- was developed to provide a more nuanced picture of POR and to guide physicians in the management of such patients. The new standards are provoking as they challenge the current terminology of POR in favor of the newly defined concept of 'low prognosis'. This article provides readers a critical appraisal of the existing criteria that standardize the definition of POR and explains the primary reasons for the development of the Poseidon criteria.